2014
DOI: 10.1371/journal.pone.0093569
|View full text |Cite
|
Sign up to set email alerts
|

Echicetin Coated Polystyrene Beads: A Novel Tool to Investigate GPIb-Specific Platelet Activation and Aggregation

Abstract: von Willebrand factor/ristocetin (vWF/R) induces GPIb-dependent platelet agglutination and activation of αIIbβ3 integrin, which also binds vWF. These conditions make it difficult to investigate GPIb-specific signaling pathways in washed platelets. Here, we investigated the specific mechanisms of GPIb signaling using echicetin-coated polystyrene beads, which specifically activate GPIb. We compared platelet activation induced by echicetin beads to vWF/R. Human platelets were stimulated with polystyrene beads coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Silver staining and mass spectrometry analysis were performed in order to confirm the purity of echicetin. Echicetin beads (EB) were prepared as reported [39] and coated for all experiments used with 0.3 mg/ml echicetin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver staining and mass spectrometry analysis were performed in order to confirm the purity of echicetin. Echicetin beads (EB) were prepared as reported [39] and coated for all experiments used with 0.3 mg/ml echicetin.…”
Section: Methodsmentioning
confidence: 99%
“…The possible reasons for the often discrepant data and results published for GPIb signaling in human platelets are well reviewed and include the use of various GPIb-V-IX complex ligands, cell types, and biochemical and functional read-out systems [20, 38]. Recently, we developed a GPIbα-specific agonist, the C-type lectin snake venom protein, echicetin, coated on polystyrene beads [39]. Earlier studies showed that echicetin molecules cross-linked by plasma IgMκ caused platelet agglutination and weak aggregation whereas echicetin monomers, when used as specific GPIbα ligands, competed with vWF and thrombin for binding to GPIbα and blocked ristocetin/vWF mediated platelet agglutination [40].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation of washed human platelets was monitored by light transmission aggregometry (LTA) using an Apact4S Plus aggregometer (DiaSys Greiner, Flacht, Germany). Platelets were stimulated by ADP (Sigma-Aldrich, Saint Louis, MO, USA), convulxin (Enzo life sciences, Lausen, Switzerland), echicetin beads (EB) (prepared as previously described [28,53]), or PDBu (Sigma-Aldrich, Saint Louis, MO, USA) under stirring conditions (1000 s −1 ) at 37 • C. Platelets were pre-treated with different effectors prior to stimulation: Src family kinase inhibitor PP2 (Abcam, Cambridge, UK), Syk inhibitors OXSI-2 (Merck, Darmstadt, Germany) and PRT-060318 (Sellckem, Houston, TX, USA), PKC pan-inhibitor GF109203X (Enzo life sciences, Lausen, Switzerland), or cAMP-elevating agent iloprost (Bayer AG, Leverkusen, Germany).…”
Section: Platelet Aggregometrymentioning
confidence: 99%
“…Several SV-CLRPs were identified to inhibit GPIb and antagonistically block vWF-induced platelet aggregation (Figure 3). Among them are agkisacutacin, agkicetin C, and akitonin, all three from Agkistridon acutus [107,108,109,110,111], flavicetin, tokaracetin, and TSV-GPIb-pb from Trimeresurus flavoviridis , Trimeresurus/Protobothrops tokarensis , and Trimeresurus stejnegeri , respectively [112,113,114], jararaca GPIb-bp from Bothrops jararaca [112,115], lebecetin from Macrovipera lebetina [116], echicetin from Echis carinatus [117,118,119], and rhodocetin subunit αβ from Calloselasma rhodostoma [120]. In contrast, some SV-CLRPs were reported to agglutinate platelets via binding to GPIb: agglucetin from Agkistrodon acutus [51,52], alboaggregin-B from Trimeresurus albolabris [121,122,123], mucrocetin and mucetin from Trimeresurus mucrosquamatus [53,124], as well as jerdonuxin from Trimeresurus/Protobothrops jerdonii [125].…”
Section: Snake Venom-c-type Lectin-related Protein (Sv-clrps)/snacmentioning
confidence: 99%